ANALISIS NILAI-NILAI AGAMA ISLAM DALAM PEMBELAJARAN BIOLOGI PADA MATERI EVOLUSI KELAS XII SMA NEGERI 1 PANYABUNGAN MANDAILING NATAL - Syarif Husein Pangaribuan; Fery Kurniawan; Fauziah Nasution (Journal of Innovative and Creativity, 2026)
This research is motivated by the importance of integrating Islamic religious values in science learning so that students are not only intellectually intelligent but also have a religious character. The focus of this research is on the implementation of Islamic values in Biology learning, especially the material on evolution which is often considered contrary to the teachings of creation in Islam. The purpose of this study is to describe the Islamic values that can be integrated and how they are applied in the learning process in grade XII of SMA Negeri 1 Panyabungan Mandailing Natal. The research used a descriptive qualitative method with observation, interview, and documentation techniques. The results showed that teachers have successfully integrated Islamic values such as monotheism, gratitude, scientific honesty, and responsibility through reflective discussions, scientific inquiry methods, and learning media that display verses from the Qur'an. This integration makes learning more meaningful because it fosters an understanding that science and religion can work together and strengthens students' faith in the greatness of Allah SWT's creation. Thus, it is recommended that teachers continue to develop learning strategies that are able to integrate science and Islamic values to create a complete learning with an Islamic character.